2006 IEEE 17th International Symposium on Personal, Indoor and Mobile Radio Communications 2006
DOI: 10.1109/pimrc.2006.254333
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Array Processing for Time-Varying Interference Mitigation in IEEE 802.16 Systems

Abstract: In this work, we propose an adaptive technique for interference mitigation based on Minimum Variance Distortionless Response (MVDR) beamforming for the uplink of a WiMAXcompliant system. This method is designed to cope with timevarying interference due to the asynchronous access of users in the neighboring cells. Channel parameters needed for beamforming are obtained by exploiting both the preambles in the transmitted frames and the pilot subcarriers embedded in each information-bearing OFDM symbol. The effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…This increases the range and reduces the number of base stations required to cover a given area. An adaptive beamformer for the uplink WiMAX compliant system was proposed in [6], which has demonstrated its ability to cope with time varying interference effectively. For WiFi in maritime scenarios, it has been shown in [6] that if a sectorized antenna is employed instead of an omni-directional antenna, the distance tested in a boat-to-air experiment can be at least doubled.…”
Section: Pervasive Adaptive Beamforming Techniques For Wireless Commumentioning
confidence: 99%
“…This increases the range and reduces the number of base stations required to cover a given area. An adaptive beamformer for the uplink WiMAX compliant system was proposed in [6], which has demonstrated its ability to cope with time varying interference effectively. For WiFi in maritime scenarios, it has been shown in [6] that if a sectorized antenna is employed instead of an omni-directional antenna, the distance tested in a boat-to-air experiment can be at least doubled.…”
Section: Pervasive Adaptive Beamforming Techniques For Wireless Commumentioning
confidence: 99%
“…Conventional training-based space-time IC techniques may not be efficient in this situation. One example of such a scenario is interference mitigation on the uplink of a cellular WIMAX-compliant system based on the IEEE 802.16-2004 [7] or ETSI HiperMAN [8] standards addressed in [9].…”
Section: Introductionmentioning
confidence: 99%
“…A non-stationary IC solution is presented in [9] in the case of a flat fading assumption for the CCI, where the interference statistic can be estimated on-line using averaging over the tracking sub-carriers of an OFDM system.…”
Section: Introductionmentioning
confidence: 99%
“…Normally, this is the case for the synchronous CCI, which has the same time-frequency structure as the desired user. Asynchronous cells, packed transmission, interference avoidance schemes, and other techniques lead to more complicated asynchronous or intermittent CCI scenarios [1] - [3] and others, where the interference may partially overlap or not overlap with the training data of the desired signal. For example, a cross-layer analysis in [2] demonstrated that this kind of interference is especially relevant for visiting (distant) users in an Open Access Network (OAN) built on wireless local area network (WLAN) with medium access control (MAC) based on carrier sensing multiple access with collision avoidance (CSMA/CA).…”
Section: Introductionmentioning
confidence: 99%